(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the efficacy and safety of sofosbuvir (SOF) and ribavirin (RBV) in the treatment of chronic Hepatitis C virus (HCV) infection Genotype-3 of multi-transfused children aged 4 to 12 years. Study Design: A Quasi-Experimental study. Place and Duration of Study: This study was conducted at the Department of Pediatric Gastroenterology and Hepatology, The Children’s Hospital & Institute of Child Health, Multan from July 2021 to October 2022. Materials and Methods: Children of either gender, aged 4 to 12 years, having HCV genotype-3 and receiving multiple transfusions (> 10 transfusions) were recruited. Children below or equal to 18 kg weight received SOF 200 mg and RBV 15 mg/kg/day while children above 18 kg received SOF 400 mg and RBV 15 mg/kg/day. Efficacy was observed as sustained viral response (SVR) after 12 weeks therapy. Results: In a total of 28 children, 18 (64.3%) were boys and 10 (35.7%) girls. The mean age was 8.38±3.51 years ranging between 4 to 12 years. Treatment was initiated and children were followed over 12 weeks. None of the children had cirrhosis. The mean hemoglobin and Fibro scan scores were 9.81±0.54 g/dl and 6.98±1.93 respectively. Transfusion requirement was not increased during treatment. On follow up, combination treatment ensured, readjusted and completed for 12-weeks. In both groups, all 28 (100%) children achieved SVR-12. During the course of the study, none of the children reported any serious treatment related side effects. None of the children experiencing treatment related side effects required any kinds of additional drugs. Conclusion: Treatment of multi-transfused children aged between 4-12 years having HCV genotype-3 with SOF and RBV was highly effective, safe and well tolerated.